Identification and characterization of Toll-like receptor 14d in Northeast Chinese lamprey (Lethenteron morii) - Zhou, Zebin; Ding, Shaoqing; Wang, Yaqian; Ren, Janfeng; Zhang, Xiangyang; Li, Weiming; Zhang, Qinghua (Frontiers in Immunology, 2023)
Toll-like receptors (TLRs) play an important role in innate immunity of defense against bacterial or viral pathogens. To study the biological characteristics and functions of the TLR genes, TLR14d was identified from Northeast Chinese lamprey (Lethenteron morii) and named LmTLR14d. LmTLR14d coding sequence (cds) is 3285 bp in length and encodes 1094 amino acids (aa). The results showed that LmTLR14d has the typical structure of TLR molecule, which contain the extracellular domain of leucine-rich repeats (LRR), transmembrane domain, and intracellular domain of Toll/interleukin-1 receptor (TIR). The phylogenetic tree showed that LmTLR14d is a homologous gene of TLR14/18 in fish. Quantitative real-time PCR (qPCR) revealed that LmTLR14d was expressed in various healthy tissues, including immune and non-immune tissues. Pseudomonas aeruginosa infection up-regulated LmTLR14d in the supraneural body (SB), gill, and kidney tissues of infected Northeast Chinese lamprey. Immunofluorescence results showed that LmTLR14d was located in the cytoplasm of HEK 293T cells in clusters, and its subcellular localization was determined by the TIR domain. The immunoprecipitation results showed that LmTLR14d could recruit LmMyD88 but not LmTRIF. Dual luciferase reporter results showed that LmTLR14d significantly enhanced the activity of the LmNF-B promoter. Furthermore, co-transfection of LmTLR14d with MyD88 significantly enhanced the LmNF-B promoter activity. LmTLR14d can induce the expression of inflammatory cytokine genes il-6 and tnf- downstream of NF-B signal. This study suggested that LmTLR14d might play an important role in the innate immune signal transduction process of lamprey and revealed the origin and function of fish-specific TLR14.